The data asset : how smart companies govern their data for business success - Fisher, Tony (Anthony), 1958- (Hoboken, N.J. : John Wiley & Sons, 2009)
An indispensable guide that shows companies how to treat data as a strategic assetOrganizations set their business strategy and direction based on information that is available to executives. The Data Asset provides guidance for not only building the business case for data quality and data governance, but also for developing methodologies and processes that will enable your organization to better treat its data as a strategic asset. Part of Wiley's SAS Business Series, this book looks at Business Case Building; Maturity Model and Organization Capabilities; 7-Step Programmatic Approach for Succe.
Making the case for better data -- Risk mitigation : how quality data keeps your company out of trouble -- Controlling costs with accurate and reliable data -- Optimizing revenue with quality data -- Governing your data -- Undisciplined organizations : a disaster waiting to happen -- Reactive organizations : trying to get beyond crisis mode -- Proactive organizations : reducing risk, avoiding uncertainty -- Governed organizations : trust in data pays multiple benefits -- The quality culture -- People -- Processes -- Undisciplined organizations : discovering the value of data quality tools -- Reactive organizations : choose the technology that gets the most from your applications -- Proactive organizations : bridging the chasm and becoming proactive -- Governed organizations : moving beyond data to business process automation.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Database management; Business intelligence; Corporate governance; x; Gouvernement d'entreprise.; COMPUTERS -- Database Management -- General; COMPUTERS -- Desktop Applications -- Databases; COMPUTERS -- System Administration -- Storage & Retrieval; Business intelligence; Corporate governance; Database management